Increase in Lipoxygenase Activity in Hairy Roots of Ambrosia maritima after Elicitation with Methyl Jasmonate (Plant Tissue Culture and Biotechnology, 2013)
Hairy roots of Ambrosia maritima L. were cultured in MS in the dark. Time course production was studied for pentayneene and thiarubine A after addition of 40 ?M methyl jasmonate to the 13?day?old hairy roots. The levels of pentayneene and thiarubrine A showed maximum increase after 72 hrs adding methyl jasmonate. Lipoxygenase activity was increased in the hairy roots elicited with 40 ?M methyl jasmonate. The increase in activity was 28?fold higher than control cultures 24 hrs after elicitor addition. The increase in enzyme activity was concomitant with the increase in pentayeneene, the precursor for polyacetylene biosynthesis. N?propyl gallate, a potent in vivo and in vitro lipoxygenase inhibitor, reduced polyacetylene production by the hairy roots at concentration of 100 ?M. It is suggested that lipoxygenase may be at least partially involved in polyacetylene biosynthesis in A. maritima hairy roots.Plant Tissue Cult. & Biotech. 23(1): 31?38, 2013 (June)DOI: http://dx.doi.org/10.3329/ptcb.v23i1.15557